PENGARUH KETELADANAN GURU PAI TERHADAP KARAKTER SISWA DI SMKN 1 RAO SELATAN - Nani Selvia; Iswantir Iswantir (Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this study was to determine whether there was an effect of the role model of Islamic Religious Education teachers on the character of students at SMKN 1 Rao Selatan. The author conducted this research because the author found several problems with the character of students at SMKN 1 Rao Selatan. Where the problem is, students often argue against what the teacher says, lack of student ethics towards teachers who are teaching, sometimes they chat behind their backs, sometimes ask for permission to leave and students often say disrespectful words to friends in front of the teacher. The type of research used by the author is correlation, with quantitative data processing. The population taken is class X² majoring in multimedia and sampling using a total sampling technique which means using the entire population, namely class X2 majoring in multimedia as a sample of 25 students. The research instrument was in the form of a questionnaire or questionnaire and processed using Statistical Product and Service Solution (SPSS) version 16. Based on the hypothesis test, the results of this study were obtained Fcount > Ftable (6.035 4.26) with a significant level below 0.05 (0 .02 0.05). It can be concluded that there is a significant influence between the exemplary variables of Islamic Religious Education teachers (X) on the student character variables (X), meaning Ha is accepted and Ho is rejected. Keyword: PAI teacher exemplary, student character